Preparation method of Cu / CNTs epoxy resin composite material with electric conduction, heat conduction and mechanical properties

By uniformly dispersing carboxylated single-wall carbon nanotubes and copper nanoparticles in the epoxy resin, forming Cu/CNTs epoxy resin composite materials, the problems of insufficient thermal conductivity, poor toughness and insufficient heat resistance of epoxy resin materials are solved, and high-performance electrical conductivity, thermal conductivity and mechanical properties are achieved.

CN119708763APending Publication Date: 2025-03-28厦门华碳科技有限公司
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411658087.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing epoxy resin materials have problems such as insufficient thermal conductivity, poor toughness and insufficient heat resistance in electronic packaging, and carbon nanotubes are prone to agglomeration in epoxy resin, affecting thermal conductivity and electrical conductivity.

Method used

By carboxylated single-walled carbon nanotubes and bonded with copper nanoparticles, Cu/CNTs epoxy resin composite is formed. The Cu/CNTs are uniformly dispersed in the epoxy resin through ultrasonic dispersion and high-temperature surface reduction methods, enhancing its electrical conductivity, thermal conductivity and mechanical properties.

Benefits of technology

It realizes the excellent mechanical, electrical and thermal conductivity of Cu/CNTs epoxy resin composite materials, meets the high-performance requirements of electronic devices for materials, and extends the service life of electronic and electrical products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119708763A_ABST
    Figure CN119708763A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a Cu / CNTs epoxy resin composite material with electric conduction, heat conduction and mechanical properties, uniformly distributed copper nanoparticles are generated on the surface of a single-walled carbon nanotube through a high-temperature surface reduction method, the prepared Cu / CNTs are uniformly dispersed in an epoxy resin component, and the weight ratio of the Cu / CNTs in the whole composite material is 1-4 wt%. The method has the advantages of simple steps and mild conditions, Cu / CNTs is uniformly dispersed in an epoxy resin matrix as a nanofiller, the electric conductivity, heat conductivity and mechanical properties of the epoxy resin composite material are effectively improved, and the material can solve the problems of heat dissipation and antistatic properties of electronic components, so that the service life of electronic and electrical products is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of composite materials, and in particular to a CNTs / Cu epoxy resin composite material having electrical conductivity, thermal conductivity and mechanical properties and a preparation method thereof. Background Art

[0002] The electronic information industry has become a pillar industry in today's world, and integrated circuit chips (IC) have experienced rapid development and wide application. my country's information industry's medium- and long-term plan for 2020 clearly puts forward the important position of new, high-density integrated circuit packaging and electronic packaging material technology. Electronic packaging is the process of mounting semiconductor devices and other microcomponents on a frame or substrate, completing electrical connections, and fixing and sealing them through insulating media to form an overall three-dimensional structured electronic product. Its main functions include fixed support, protecting the chip from external moisture and dust, and also having heat dissipation function. At present, 90% of electronic packaging uses epoxy resin as material. Epoxy resin is one of the common matrix materials in polymer composites. It is widely used in electrical, electronic, adhesive and composite materials because of its comprehensive properties such as high mechanical strength, low volume shrinkage, low dielectric constant, strong creep resistance and strong adhesion. However, its poor toughness and insufficient heat resistance are the main disadvantages of epoxy resin.

[0003] Carbon nanotubes are considered to be ideal fillers for preparing high-performance epoxy resin composites. At room temperature, the axial thermal conductivity of single-walled carbon nanotubes and multi-walled carbon nanotubes is 6600 and 3000 W / m·K respectively. The results show that the heat transfer mechanism of carbon nanotubes is mainly phonon conduction mode. Phonons in carbon nanotubes have a fast transfer rate and a long free path, and their transmission process is similar to ballistic transmission. The excellent thermal conductivity of carbon nanotubes is closely related to their unique structure, in which sp 2 There is strong rigidity between hybridized carbon atoms. Therefore, the thermal conductivity of epoxy resin composites can be effectively improved by adding a small amount of carbon nanotubes. Carbon nanotubes have excellent mechanical, electrical and thermal properties, and have structural characteristics such as high aspect ratio, low density, high tensile strength and high elastic modulus. Compounding carbon nanotubes with epoxy resin is expected to improve the mechanical properties as well as thermal, electrical and other properties of epoxy resin composites. The graphite-like structure of carbon nanotubes gives them high thermal and electrical conductivity, and can be used as excellent thermal and electrical conductive fillers, and is widely used in fields such as electronic component packaging.

[0004] However, carbon nanotubes themselves are easy to entangle and have high surface activity, which makes them easy to agglomerate in epoxy resin, thus adversely affecting the improvement of thermal and electrical conductivity of the composite material. Summary of the invention

[0005] The present application is made in view of the above-mentioned problems, and its purpose is to provide a method for preparing a Cu / CNTs epoxy resin composite material having electrical conductivity, thermal conductivity and mechanical properties. Through this preparation method, Cu / CNTs are uniformly dispersed in the epoxy resin matrix, thereby achieving the reinforcement and modification of the epoxy resin material by single-walled carbon nanotubes, and the prepared composite material has excellent mechanical and electrical conductivity properties, which greatly meets the requirements of electronic devices for materials.

[0006] In order to solve the above problems, the present invention provides a method for preparing a Cu / CNTs epoxy resin composite material having electrical conductivity, thermal conductivity and mechanical properties, comprising the following steps:

[0007] (1) Carboxylation of single-walled carbon nanotubes;

[0008] (2) Preparation of Cu / CNTs;

[0009] (3) Preparation of Cu / CNTs epoxy resin dispersion;

[0010] (4) Preparation of Cu / CNTs epoxy resin composites.

[0011] In any embodiment, the carboxylation of the single-walled carbon nanotubes in step (1) comprises:

[0012] Weigh single-walled carbon nanotubes and place them in a three-necked flask, add concentrated H2SO4 and concentrated HNO3 in a certain volume ratio, and place them in a water bath at 50-60°C for ultrasonic treatment for 2-3 hours; dilute the solution with deionized water, let it stand until the solution is separated, pour out the upper clear liquid, and wash and filter the black suspension at the bottom with deionized water until the pH is 7; place the filtered product in a vacuum drying oven at 70-90°C and dry it to constant weight to obtain carboxylated single-walled carbon nanotubes.

[0013] In any embodiment, the volume ratio of concentrated H2SO4 to concentrated HNO3 in step (1) is 3:1.

[0014] In any embodiment, the preparation of Cu / CNTs in step (2) comprises:

[0015] The carboxylated single-walled carbon nanotubes are dispersed in deionized water, a copper chloride solution is added, and the mixture is heated at 60 to 80°C with continuous stirring for 3 to 4 hours. After the reaction is completed, the (SWCNT-COO)-Cu solid product is collected by centrifugation and vacuum dried at 60 to 80°C. After the drying is completed, the solid product is treated at a high temperature of 200 to 300°C in a H2 atmosphere.

[0016] The carboxylated carbon nanotubes are dispersed in deionized water and grafted with copper chloride; high temperature treatment reduces the copper ions grafted onto the carbon nanotubes, generating copper nanoparticles on the surface of the carbon nanotubes. The copper nanoparticles are mainly deposited on the wall of the single-walled carbon nanotubes through van der Waals interactions.

[0017] In any embodiment, the ratio of the carboxylated carbon nanotubes to the copper chloride solution is 1 g: 50-100 ml, and the concentration of the copper chloride solution is 0.15-0.3M.

[0018] In any embodiment, the preparation of the Cu / CNTs epoxy resin dispersion in step (3) comprises:

[0019] The Cu / CNTs and epoxy resin are ultrasonically dispersed in an organic solvent for 2 to 4 hours to ensure that the Cu / CNTs are evenly dispersed in the epoxy resin.

[0020] In any embodiment, the organic solvent in step (3) is one of acetone, ethanol, tetrahydrofuran and acetonitrile.

[0021] In any embodiment, the epoxy resin in step (3) is bisphenol A or bisphenol F epoxy resin.

[0022] In any embodiment, the preparation of the Cu / CNTs epoxy resin composite material in step (4) comprises:

[0023] The organic solvent in the Cu / CNTs epoxy resin dispersion is removed by rotary evaporation, and then the curing agent is added and stirred with a stirrer for 5 to 10 minutes to make the Cu / CNTs epoxy resin composite material mixed evenly; the bubbles are removed in a vacuum oven and poured into a mold; finally, the samples are pre-cured at low temperature at 80°C to 100°C for 1 to 3 hours and at high temperature at 120 to 150°C for 2 to 4 hours in a programmed oven until the samples are completely cured.

[0024] In any embodiment, the curing agent in step (4) is one or two of 4,4'-diaminodiphenylmethane, 2-ethyl-4-methylimidazole, and phthalic anhydride.

[0025] In any embodiment, the weight ratio of the curing agent to the epoxy resin is 0.1 to 0.3.

[0026] In any embodiment, the weight proportion of the Cu / CNTs in the total composite material is 1 wt % to 4 wt %.

[0027] Beneficial effects of the present invention:

[0028] (1) The Cu / CNTs epoxy resin composite material with electrical conductivity, thermal conductivity and mechanical properties provided by the present invention has carboxyl groups grafted on the surface of single-walled carbon nanotubes, which has good dispersion performance, and is embedded in the epoxy resin matrix through covalent bonding, thereby improving the interface bonding between the single-walled carbon nanotubes and the matrix, and the Cu / CNTs are evenly dispersed in the epoxy resin matrix. In addition, in the Cu / CNTs prepared by the high-temperature surface reduction method, copper nanoparticles are evenly distributed on the surface of the carbon nanotubes. By adding a small amount of Cu / CNTs, the electrical conductivity, thermal conductivity and mechanical properties of the composite material are significantly improved.

[0029] (2) The carbon nanotubes in the epoxy resin composite material provided by the present invention form a stable and reliable connection in the epoxy resin matrix. When a break occurs, the carbon nanotubes cannot be destroyed and can only be pulled out of the matrix, which consumes a lot of energy. At the same time, the carbon nanotubes bend and deform at the break to form a bridging effect. These effects improve the strength and toughness of the composite material.

[0030] (3) The epoxy resin composite material provided by the present invention has a greatly improved dispersibility of the modified Cu / CNTs in the epoxy resin and forms a strong interaction with the epoxy matrix, making it easier to form a dense thermal conductive network and pathway. In addition, due to the additional phonon scattering of CNTs caused by the attachment of copper nanoparticles to the surface, the epoxy resin composite material has excellent thermal conductivity.

[0031] (4) The improvement in the electrical conductivity of the epoxy resin composite material provided by the present invention is due to the fact that, on the one hand, the nanofillers are interconnected in the epoxy resin matrix to form a continuous and effective conductive channel or conductive area; on the other hand, the metal nanoparticles are attached to the defect sites of the carbon nanotubes, and the contact resistance of the CNT junction in the epoxy resin matrix is ​​reduced.

[0032] (5) The epoxy resin composite material provided by the present invention has simple steps and mild conditions, and can be widely used in the fields of thermal interface materials and packaging materials for electronic components. The material can solve the problems of electronic components in terms of heat dissipation and antistatic performance, thereby preventing electronic components from suffering from electrostatic disasters and premature aging, thereby extending the service life of electronic and electrical products. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is a scanning electron microscope image of the Cu / CNTs epoxy resin composite material of the present application;

[0034] Figure 2 This is a scanning electron microscope image of the unmodified Cu / CNTs epoxy resin composite material of the comparative example;

[0035] Figure 3 Schematic diagram of copper-grafted single-walled carbon nanotubes in this application. DETAILED DESCRIPTION

[0036] Hereinafter, an embodiment of a method for preparing a Cu / CNTs epoxy resin composite material having electrical conductivity, thermal conductivity and mechanical properties of the present application will be specifically disclosed in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0037] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values ​​or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0038] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0039] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0040] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0041] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0042] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0043] A method for preparing a Cu / CNTs epoxy resin composite material having electrical conductivity, thermal conductivity and mechanical properties, comprising the following steps:

[0044] (1) Carboxylation of single-walled carbon nanotubes;

[0045] (2) Preparation of Cu / CNTs;

[0046] (3) Preparation of Cu / CNTs epoxy resin dispersion;

[0047] (4) Preparation of Cu / CNTs epoxy resin composites.

[0048] In some embodiments, the specific process of carboxylation of the single-walled carbon nanotubes in step (1) above includes:

[0049] Weigh single-walled carbon nanotubes and place them in a three-necked flask, add concentrated H2SO4 and concentrated HNO3 in a certain volume ratio, and place them in a water bath at 50-60°C for ultrasonic treatment for 2-3 hours; dilute the solution with deionized water, let it stand until the solution is separated, pour out the upper clear liquid, and wash and filter the black suspension at the bottom with deionized water until the pH is 7; place the filtered product in a vacuum drying oven and dry it at 80°C to constant weight to obtain carboxylated single-walled carbon nanotubes.

[0050] In some embodiments, the volume ratio of concentrated H2SO4 to concentrated HNO3 in step (1) is 3:1.

[0051] In some embodiments, the specific process of preparing Cu / CNTs in the above step (2) includes:

[0052] 1g of carboxylated carbon nanotubes was dispersed in 100ml of deionized water. Then, 100mL of 0.2M copper chloride (CuCl2) solution was added to the dispersant and heated with continuous stirring at 60-80°C for 3-4 hours. Next, the (SWCNT-COO)-Cu solid product was collected by centrifugation and vacuum dried at 60-80°C; then, the copper ions grafted onto the carbon nanotubes were reduced at 200-300°C in a H2 atmosphere to produce copper nanoparticles on the surface of the carbon nanotubes. The copper nanoparticles were mainly deposited on the walls of the single-walled carbon nanotubes through van der Waals interactions.

[0053] During the drying process, the copper ions generated on the surface of the carbon nanotubes are reduced to copper nanoparticles and adhere to the surface via van der Waals forces.

[0054] The (SWCNT-COO)-Cu solid product is dried at 60-80°C to remove water; copper ions are reduced to copper nanoparticles under hydrogen and high temperature conditions; when the temperature is too high, the reaction rate will increase, but it will also increase the possibility of side reactions. At extremely high temperatures, the reduction reaction of copper ions may proceed excessively, resulting in the formation of unstable intermediates or by-products. This may reduce the efficiency of the reduction reaction and increase the content of impurities in the product. In contrast, when the temperature is too low, the rate of the reduction reaction slows down. This may prolong the reaction time and increase the possibility of other adverse reactions. In addition, too low a temperature may also cause the reduction reaction to fail to proceed completely, thereby affecting the purity and yield of the product.

[0055] In some embodiments, the ratio of the carboxylated carbon nanotubes to the copper chloride solution is 1 g: 50-100 ml, and the concentration of the copper chloride solution is 0.15-0.3M.

[0056] The surface of carboxylated carbon nanotubes has a large number of carboxyl (-COOH) clusters, which have a certain hydrophilicity and can react with metal ions. The copper ions (Cu2+) in the copper chloride (CuCl2) solution can react with the carboxyl groups on the surface of carbon nanotubes to form a complex. The complexing ability of copper ions is such that within a certain concentration range, copper ions can effectively complex with the carboxyl groups on the surface of carboxylated carbon nanotubes. Too many copper ions may lead to complexation supersaturation, which makes it impossible to effectively combine with carbon nanotubes. Instead, precipitation of copper ions or other side reactions may occur. In addition, too high a concentration of copper ions may cause ion aggregation in the solution, affecting the dispersibility of carbon nanotubes. Too low a concentration may not fully form a complex of copper and carbon nanotubes, and the reaction effect is not good.

[0057] In some embodiments, the specific process of preparing the Cu / CNTs epoxy resin dispersion in step (3) above includes:

[0058] The Cu / CNTs and epoxy resin are ultrasonically dispersed in an organic solvent for 2 to 4 hours to ensure that the Cu / CNTs are uniformly dispersed in the epoxy resin.

[0059] In some embodiments, the Cu / CNTs addition amount is 1:1 of the epoxy resin. ~ 4wt%. Too little addition will not achieve the reinforcing effect, while too much addition will cause agglomeration and affect the performance.

[0060] In some embodiments, the organic solvent in step (3) is one of acetone, ethanol, tetrahydrofuran, and acetonitrile.

[0061] In some embodiments, the epoxy resin in step (3) is bisphenol A or bisphenol F epoxy resin.

[0062] In some embodiments, the specific process of preparing the Cu / CNTs epoxy resin composite material in the above step (4) includes:

[0063] The organic solvent in the Cu / CNTs epoxy resin dispersion was removed by rotary evaporation, and then the curing agent was added and stirred with a stirrer for 5 to 10 minutes to ensure that the Cu / CNTs epoxy resin composite material was mixed evenly. The bubbles were removed in a vacuum oven and poured into a mold. Finally, the sample was pre-cured at low temperature at 80°C to 100°C for 1 to 3 hours and high temperature at 120 to 150°C for 2 to 4 hours in a programmed oven until the sample was completely cured.

[0064] The curing temperature of epoxy resin needs to be within a specific range because the curing temperature directly affects the rate and effect of the curing reaction. If the curing temperature is too low, the curing reaction rate will slow down, resulting in a longer curing time, and may even fail to fully cure; while a curing temperature that is too high may cause the curing reaction to be too fast, causing problems such as increased internal stress and uneven shrinkage of the material. Therefore, controlling the curing temperature within a suitable range can ensure that the curing reaction proceeds smoothly and ultimately obtain a cured product with good performance.

[0065] In some embodiments, the curing agent in step (4) is one or two of 4,4'-diaminodiphenylmethane, 2-ethyl-4-methylimidazole, and phthalic anhydride.

[0066] In some embodiments, the ratio of the added amount of the curing agent to the epoxy resin is 10 g / 100 g to 30 g / 100 g.

[0067] This ensures that the amount of functional groups contained in the curing agent matches the amount of epoxy groups in the epoxy resin, allowing the epoxy resin to open its ring to form a cross-linked network and obtain the best curing effect and performance.

[0068] In some embodiments, the Cu / CNTs account for 1 wt% to 4 wt% of the total composite material. If the amount added is too little, the reinforcement effect is not obvious, and if the amount added is too much, the Cu / CNTs are prone to agglomeration, which has a negative impact on the performance improvement.

[0069] Example

[0070] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0071] Example 1

[0072] A Cu / CNTs epoxy resin composite material having both electrical conductivity and mechanical properties and a preparation method thereof, comprising the following steps:

[0073] (1) Carboxylation of single-walled carbon nanotubes

[0074] Weigh single-walled carbon nanotubes and place them in a three-necked flask, add concentrated H2SO4 and concentrated HNO3 in a volume ratio of 3:1, and place them in a 60°C water bath for ultrasonic treatment for 2 hours; dilute the solution with deionized water, let it stand until the solution is separated, pour out the upper clear liquid, and wash and filter the black suspension at the bottom with deionized water until the pH is 7; place the filtered product in a vacuum drying oven and dry it at 80°C to constant weight to obtain carboxylated single-walled carbon nanotubes.

[0075] (2) Preparation of Cu / CNTs

[0076] 1g of carboxylated carbon nanotubes was dispersed in 100ml of deionized water. Then, 100mL of 0.2M copper chloride (CuCl2) solution was added to the dispersant and heated at 80°C for 3h with continuous stirring. Next, the (SWCNT-COO)-Cu solid product was collected by centrifugation and vacuum dried at 60°C. Copper nanoparticles were generated on the surface of carbon nanotubes at 200°C in a H2 atmosphere.

[0077] (3) Preparation of Cu / CNTs epoxy resin dispersion

[0078] Cu / CNTs and 100 g of bisphenol A epoxy resin were ultrasonically dispersed in acetone solvent for 2 h to ensure that Cu / CNTs were uniformly dispersed in the epoxy resin. The addition amount of Cu / CNTs in the bisphenol A epoxy resin composite material was 1 wt%.

[0079] (4) Preparation of Cu / CNTs epoxy resin composites

[0080] The acetone solvent in the Cu / CNTs epoxy resin dispersion was removed by rotary evaporation, and then 25 g of curing agent 4,4'-diaminodiphenylmethane was added and stirred for 10 min using a stirrer to ensure that the Cu / CNTs epoxy resin composite was mixed evenly. The bubbles were removed in a vacuum oven and poured into a mold. Finally, the sample was pre-cured at 100 ° C for 1 h and at 150 ° C for 2 h in a programmed oven until the sample was completely cured.

[0081] Example 2

[0082] A Cu / CNTs epoxy resin composite material having both electrical conductivity and mechanical properties and a preparation method thereof, comprising the following steps:

[0083] (1) Carboxylation of single-walled carbon nanotubes

[0084] Weigh single-walled carbon nanotubes and place them in a three-necked flask, add concentrated H2SO4 and concentrated HNO3 in a volume ratio of 3:1, and place them in a 60°C water bath for ultrasonic treatment for 2 hours; dilute the solution with deionized water, let it stand until the solution is separated, pour out the upper clear liquid, and wash and filter the black suspension at the bottom with deionized water until the pH is 7; place the filtered product in a vacuum drying oven and dry it at 80°C to constant weight to obtain carboxylated single-walled carbon nanotubes.

[0085] (2) Preparation of Cu / CNTs

[0086] 1g of carboxylated carbon nanotubes was dispersed in 100ml of deionized water. Then, 100mL of 0.2M copper chloride (CuCl2) solution was added to the dispersant and heated at 80°C for 3h with continuous stirring. Next, the (SWCNT-COO)-Cu solid product was collected by centrifugation and vacuum dried at 60°C. Copper nanoparticles were generated on the surface of carbon nanotubes at 200°C in a H2 atmosphere.

[0087] (3) Preparation of Cu / CNTs epoxy resin dispersion

[0088] Cu / CNTs and 100 g of bisphenol A epoxy resin were ultrasonically dispersed in acetone solvent for 2 h to ensure that Cu / CNTs were uniformly dispersed in the epoxy resin. The addition amount of Cu / CNTs in the bisphenol A epoxy resin composite material was 2 wt%.

[0089] (4) Preparation of Cu / CNTs epoxy resin composites

[0090] The acetone solvent in the Cu / CNTs epoxy resin dispersion was removed by rotary evaporation, and then 25 g of curing agent 4,4'-diaminodiphenylmethane was added and stirred for 10 min using a stirrer to ensure that the Cu / CNTs epoxy resin composite was mixed evenly. The bubbles were removed in a vacuum oven and poured into a mold. Finally, the sample was pre-cured at 80 ° C for 3 h in a programmed oven and cured at 120 ° C for 4 h until the sample was completely cured.

[0091] Example 3

[0092] A Cu / CNTs epoxy resin composite material having both electrical conductivity and mechanical properties and a preparation method thereof, comprising the following steps:

[0093] (1) Carboxylation of single-walled carbon nanotubes

[0094] Weigh single-walled carbon nanotubes and place them in a three-necked flask, add concentrated H2SO4 and concentrated HNO3 in a volume ratio of 3:1, and place them in a 60°C water bath for ultrasonic treatment for 2 hours; dilute the solution with deionized water, let it stand until the solution is separated, pour out the upper clear liquid, and wash and filter the black suspension at the bottom with deionized water until the pH is 7; place the filtered product in a vacuum drying oven and dry it at 80°C to constant weight to obtain carboxylated single-walled carbon nanotubes.

[0095] (2) Preparation of Cu / CNTs

[0096] 1g of carboxylated carbon nanotubes was dispersed in 100ml of deionized water. Then, 100mL of 0.2M copper chloride (CuCl2) solution was added to the dispersant and heated at 80°C for 3h with continuous stirring. Next, the (SWCNT-COO)-Cu solid product was collected by centrifugation and vacuum dried at 60°C. Copper nanoparticles were generated on the surface of carbon nanotubes at 200°C in a H2 atmosphere.

[0097] (3) Preparation of Cu / CNTs epoxy resin dispersion

[0098] Cu / CNTs and 100 g of bisphenol A epoxy resin were ultrasonically dispersed in acetone solvent for 2 h to ensure that Cu / CNTs were uniformly dispersed in the epoxy resin. The addition amount of Cu / CNTs in the bisphenol A epoxy resin composite material was 3 wt%.

[0099] (4) Preparation of Cu / CNTs epoxy resin composites

[0100] The acetone solvent in the Cu / CNTs epoxy resin dispersion was removed by rotary evaporation, and then 25 g of curing agent 4,4'-diaminodiphenylmethane was added and stirred for 10 min using a stirrer to ensure that the Cu / CNTs epoxy resin composite was mixed evenly. The bubbles were removed in a vacuum oven and poured into a mold. Finally, the sample was pre-cured at 100 ° C for 2 h in a programmed oven and cured at 150 ° C for 2 h until the sample was completely cured.

[0101] Example 4

[0102] A Cu / CNTs epoxy resin composite material having both electrical conductivity and mechanical properties and a preparation method thereof, comprising the following steps:

[0103] (1) Carboxylation of single-walled carbon nanotubes

[0104] Weigh single-walled carbon nanotubes and place them in a three-necked flask, add concentrated H2SO4 and concentrated HNO3 in a volume ratio of 3:1, and place them in a 60°C water bath for ultrasonic treatment for 2 hours; dilute the solution with deionized water, let it stand until the solution is separated, pour out the upper clear liquid, and wash and filter the black suspension at the bottom with deionized water until the pH is 7; place the filtered product in a vacuum drying oven and dry it at 80°C to constant weight to obtain carboxylated single-walled carbon nanotubes.

[0105] (2) Preparation of Cu / CNTs

[0106] 1g of carboxylated carbon nanotubes was dispersed in 100ml of deionized water. Then, 100mL of 0.2M copper chloride (CuCl2) solution was added to the dispersant and heated at 80°C for 3h with continuous stirring. Next, the (SWCNT-COO)-Cu solid product was collected by centrifugation and vacuum dried at 60°C. Copper nanoparticles were generated on the surface of carbon nanotubes at 200°C in a H2 atmosphere.

[0107] (3) Preparation of Cu / CNTs epoxy resin dispersion

[0108] Cu / CNTs and 100 g of bisphenol A epoxy resin were ultrasonically dispersed in acetone solvent for 2 h to ensure that Cu / CNTs were uniformly dispersed in the epoxy resin. The addition amount of Cu / CNTs in the bisphenol A epoxy resin composite material was 4 wt%.

[0109] (4) Preparation of Cu / CNTs epoxy resin composites

[0110] The acetone solvent in the Cu / CNTs epoxy resin dispersion was removed by rotary evaporation, and then 25 g of curing agent 4,4'-diaminodiphenylmethane was added and stirred for 10 min using a stirrer to ensure that the Cu / CNTs epoxy resin composite was mixed evenly. The bubbles were removed in a vacuum oven and poured into a mold. Finally, the sample was pre-cured at 100 ° C for 1 h in a programmed oven and cured at 130 ° C for 3.5 h until the sample was completely cured.

[0111] Comparative Example 1

[0112] The steps for preparing the Cu / CNTs epoxy resin composite material were the same as those in Example 1, except that the addition amount of Cu / CNTs was 10%.

[0113] Comparative Example 2

[0114] The steps for preparing the Cu / CNTs epoxy resin composite material were the same as those in Example 1, except that the addition amount of Cu / CNTs was 0%.

[0115] Comparative Example 3

[0116] (1) Preparation of Cu / CNTs

[0117] 1g of single-walled carbon nanotubes was dispersed in 100ml of deionized water. Then, 100mL of 0.2M copper chloride (CuCl2) solution was added to the dispersant and heated at 80°C for 3h with continuous stirring. Next, the SWCNT-Cu solid product was collected by centrifugation and vacuum dried at 60°C. Copper nanoparticles were generated on the surface of carbon nanotubes at 200°C in a H2 atmosphere.

[0118] (2) Preparation of Cu / CNTs epoxy resin dispersion

[0119] Cu / CNTs and 100 g of bisphenol A epoxy resin were ultrasonically dispersed in acetone solvent for 2 h to ensure that Cu / CNTs were uniformly dispersed in the epoxy resin. The addition amount of Cu / CNTs in the bisphenol A epoxy resin composite material was 3 wt%.

[0120] (3) Preparation of Cu / CNTs epoxy resin composites

[0121] The acetone solvent in the Cu / CNTs epoxy resin dispersion was removed by rotary evaporation, and then 25 g of curing agent 4,4'-diaminodiphenylmethane was added and stirred for 10 min using a stirrer to ensure that the Cu / CNTs epoxy resin composite was mixed evenly. The bubbles were removed in a vacuum oven and poured into a mold. Finally, the sample was heated in a programmed oven at 100°C and 150°C for 2 h respectively until the sample was fully cured.

[0122] Comparative Example 4

[0123] (1) Carboxylation of single-walled carbon nanotubes

[0124] Weigh single-walled carbon nanotubes and place them in a three-necked flask, add concentrated H2SO4 and concentrated HNO3 in a volume ratio of 3:1, and place them in a 60°C water bath for ultrasonic treatment for 2 hours; dilute the solution with deionized water, let it stand until the solution is separated, pour out the upper clear liquid, and wash and filter the black suspension at the bottom with deionized water until the pH is 7; place the filtered product in a vacuum drying oven and dry it at 80°C to constant weight to obtain carboxylated single-walled carbon nanotubes.

[0125] (2) Preparation of CNTs epoxy resin dispersion

[0126] The carboxylated single-walled carbon nanotubes and 100 g of bisphenol A epoxy resin were ultrasonically dispersed in acetone solvent for 2 h to ensure that the single-walled carbon nanotubes were uniformly dispersed in the epoxy resin. The addition amount of the single-walled carbon nanotubes in the bisphenol A epoxy resin composite material was 3 wt%.

[0127] (3) Preparation of CNTs-epoxy resin composites

[0128] The acetone solvent in the CNTs epoxy resin dispersion was removed by rotary evaporation, and then 25 g of curing agent 4,4'-diaminodiphenylmethane was added and stirred for 10 min using a stirrer to ensure that the CNTs epoxy resin composite was mixed evenly. The bubbles were removed in a vacuum oven and poured into a mold. Finally, the sample was heated in a programmed oven at 100 ° C and 150 ° C for 2 h respectively until the sample was fully cured.

[0129] (A) Mechanical properties test of Cu / CNTs epoxy resin composites.

[0130] The experimental results are shown in Table 1. Table 1 is as follows:

[0131]

[0132] It can be seen from Table 1 that in Example 1-4, as the content of Cu / CNTs increases, the mechanical properties of the Cu / CNTs epoxy resin composite material show a trend of first increasing and then decreasing. When the content of Cu / CNTs is 3wt%, the mechanical properties of the material reach the maximum value. If the mass fraction of Cu / CNTs is too large, it will be difficult to disperse in the epoxy resin, and the interface bonding ability with the epoxy resin matrix will decrease, and agglomeration will occur, which will lead to a decrease in the mechanical properties of the composite material. Since the surface of the modified carbon nanotubes is grafted with carboxyl groups, the dispersion performance is good, and it is embedded in the epoxy resin matrix through covalent bonding, which improves the interface bonding between it and the matrix, changes the crack propagation path, and reduces the stress concentration of the matrix. The carbon nanotubes form a stable and reliable connection in the epoxy resin matrix. When a break occurs, the carbon nanotubes cannot be destroyed and can only be pulled out of the matrix. This process consumes a lot of energy. At the same time, at the place of the break, the carbon nanotubes bend and deform to form a bridging effect. These effects all improve the strength and toughness of the composite material. In the epoxy resin composite material of Comparative Example 3, since the carbon nanotubes are not modified, the van der Waals force is large, resulting in serious agglomeration in the matrix, and the unmodified carbon nanotubes have poor compatibility with the epoxy resin matrix, which easily forms stress concentration points during bending, increases the brittleness of the material, and thus leads to a decrease in the overall mechanical properties of the material. The tensile, bending, and impact properties of the epoxy resin composite materials of Comparative Examples 1 to 4 are all worse than those of Example 3, indicating that the Cu / CNTs epoxy resin composite material prepared by the present invention has excellent mechanical properties.

[0133] (2) Thermal conductivity test of Cu / CNTs epoxy resin composite material.

[0134] The experimental results are shown in Table 2. Table 2 is as follows:

[0135]

[0136] Traditional theory holds that heat conduction in polymer matrices is not due to the vibration of the π electron cloud, but relies on the vibration of the crystal lattice, that is, phonons are the heat energy carriers. Then in polymers, due to their generally large relative molecular mass, their molecular chains are easily entangled randomly and cannot be tightly arranged in parallel, resulting in the inability to have a complete lattice and containing amorphous components. In addition, the molecular chains will have a scattering effect on the transmission of phonons, making the free path of phonons in polymer materials very small, the thermal conductivity is low, and the thermal conductivity of the material is very poor. In order to increase the thermal conductivity of polymer composites, it is necessary to rely on the addition of high thermal conductivity fillers such as carbon nanotubes. Adding original carbon nanotubes to epoxy resin, due to the large surface inertness of the original carbon nanotubes, the poor interface performance and compatibility between the original carbon nanotubes and the poor dispersion of the original carbon nanotubes in the resin, the phonon transmission scattering is very serious in the epoxy resin, and the thermal conductivity is not significantly improved. By adding the modified Cu / CNTs, the dispersibility of the modified carbon nanotubes in the epoxy resin is greatly improved, and a strong interaction is formed between the surface-modified carbon nanotubes and the epoxy matrix, making it easier to form a dense thermal conductive network and pathway. Compared with the CNTs epoxy resin composite material in Comparative Example 4, the thermal conductivity of the Cu / CNTs epoxy resin composite material is relatively high, which is due to the additional phonon scattering of the CNTs caused by the attachment of copper nanoparticles to the surface.

[0137] (3) Test the electrical conductivity of Cu / CNTs epoxy resin composite materials.

[0138] The experimental results are shown in Table 3. Table 3 is as follows:

[0139]

[0140] Due to the special one-dimensional nanostructure of carbon nanotubes, they are very sensitive to conductivity in the axial direction, while epoxy resin is an insulating material. When carbon nanotubes are added as fillers to the epoxy resin matrix, the surface volume resistivity of the Cu / CNTs epoxy resin composite material will drop significantly when the carbon nanotube content reaches a certain level. Therefore, carbon nanotubes can improve the conductivity of the composite material. When the content of carbon nanotubes in the composite material is low, the nanofillers cannot effectively overlap to form a continuous network, resulting in the obstruction of the movement of free electrons in the composite material, which is manifested as a high resistivity of the composite material on a macroscopic scale. However, as the content of carbon nanotubes increases, the probability of nanofillers touching in the epoxy resin matrix increases sharply, and they are connected to each other to form a continuous and effective conductive channel or conductive area. The free electrons in the matrix move freely along the formed conductive channel, or jump between conductive areas to form a large conductive network, and the conductivity of the composite material increases accordingly, which is manifested as a significant decrease in the surface volume resistivity of the material on a macroscopic scale. However, when the excess carbon nanotubes form a sufficient conductive network, the synergistic effect of the increase in carbon nanotube content on the conductive properties of the material will gradually become flat. The significant improvement in the electrical properties of the Cu / CNTs epoxy composite compared to the CNTs epoxy composite in Comparative Example 4 may be attributed to the reduced contact resistance of the CNT junctions in the epoxy matrix due to the attachment of metal nanoparticles to the defect sites of the carbon nanotubes.

[0141] The scanning electron microscopy images of Example 3 and Comparative Example 3 (3 wt% unmodified Cu / CNTs added to epoxy resin) are as follows: Figure 1 and Figure 2 As shown, Cu / CNTs are evenly dispersed in the epoxy resin matrix ( Figure 1 The unmodified Cu / CNTs showed obvious agglomeration in the epoxy resin matrix ( Figure 2 shown).

[0142] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A method for preparing a Cu / CNTs epoxy resin composite material having electrical conductivity, thermal conductivity and mechanical properties, characterized in that: The following steps are involved: (1) Carboxylation of single-walled carbon nanotubes; (2) Preparation of Cu / CNTs; (3) Preparation of Cu / CNTs epoxy resin dispersion; (4) Preparation of Cu / CNTs epoxy resin composites.

2. The preparation method according to claim 1, characterized in that: The carboxylation of the single-walled carbon nanotubes in step (1) comprises: Weigh single-walled carbon nanotubes and place them in a three-necked flask, add concentrated H2SO4 and concentrated HNO3 in a certain volume ratio, and place them in a water bath at 50-60°C for ultrasonic treatment for 2-3 hours; dilute the solution with deionized water, let it stand until the solution is separated, pour out the upper clear liquid, and wash and filter the black suspension at the bottom with deionized water until the pH is 7; place the filtered product in a vacuum drying oven at 70-90°C and dry it to constant weight to obtain carboxylated single-walled carbon nanotubes.

3. The preparation method according to claim 2, characterized in that: The volume ratio of concentrated H2SO4 to concentrated HNO3 is 3:

1.

4. The preparation method according to claim 1, characterized in that: The preparation of Cu / CNTs in step (2) includes: The carboxylated carbon nanotubes are dispersed in deionized water; then, a copper chloride solution is added to the dispersant and heated at 60 to 80°C with continuous stirring for 3 to 4 hours; after the reaction is completed, the (SWCNT-COO)-Cu solid product is collected by centrifugation and vacuum dried at 60 to 80°C; then, high-temperature treatment is performed at 200 to 300°C in a H2 atmosphere.

5. The preparation method according to claim 4, characterized in that: The ratio of the carboxylated carbon nanotubes to the copper chloride solution is 1g:50-100ml, and the concentration of the copper chloride solution is 0.15 ~ 0.3M.

6. The preparation method according to claim 1, characterized in that: The preparation of the Cu / CNTs epoxy resin dispersion in step (3) comprises: The Cu / CNTs and epoxy resin are ultrasonically dispersed in an organic solvent for 2 to 4 hours to ensure that the Cu / CNTs are evenly dispersed in the epoxy resin.

7. The preparation method according to claim 6, characterized in that: The organic solvent is one of acetone, ethanol, tetrahydrofuran and acetonitrile; the epoxy resin is bisphenol A type or bisphenol F type epoxy resin.

8. The preparation method according to claim 1, characterized in that: The preparation of the Cu / CNTs epoxy resin composite material in step (4) comprises: The organic solvent in the Cu / CNTs epoxy resin dispersion is removed by rotary evaporation, and then the curing agent is added and stirred with a stirrer for 5 to 10 minutes to make the Cu / CNTs epoxy resin composite material mixed evenly; the bubbles are removed in a vacuum oven and poured into a mold; finally, the samples are pre-cured at low temperature at 80°C to 100°C for 1 to 3 hours and at high temperature at 120 to 150°C for 2 to 4 hours in a programmed oven until the samples are completely cured.

9. The preparation method according to claim 8, characterized in that: In the step (4), the curing agent is one or two of 4,4'-diaminodiphenylmethane, 2-ethyl 4-methylimidazole, and phthalic anhydride; and the weight ratio of the curing agent to the epoxy resin is 0.1 to 0.

3.

10. The preparation method according to claim 1 or 6, characterized in that: The weight proportion of the Cu / CNTs in the total composite material is 1 wt% to 4 wt%.

Citation Information

Cited By

  • Antistatic epoxy packaging film, preparation method thereof and filter chip packaging structure

    CN120399595A

  • Antistatic epoxy encapsulation film, preparation method thereof and filter chip encapsulation structure

    CN120399595B